Triumph of mental disorder for the willingness to live in the novel “Life is What You Make it” by Preeti shenoy - Kumari, Monika; Krishan, Ram (International Journal of Psychosocial Rehabilitation, 2020)
Life is What You Make it” is a motivational and inspirational work by Preeti Shenoy. She has written so many works that are very useful and meaningful. Everyone in the life faces a lot of problems and many times life make us stand at such a turn. which we cannot even imagine. In this story the protagonist, Ankita Sharma also faces a turning point which affects her life badly. Human life is not easy we have to do sometimes those things that are far from our comfort zone for the surviving on this planet. Ankita Sharma, who is a brilliant, charming girl, meets misfortune of bipolar disorder in her life that she accepts and conquers. This paper will help us to understand the value of life and how we can make it better and meaningful. Sometimes our wrong decisions bring us to such a stand, where we have nothing but regret. Ankita just wants to become an independent girl that is by she rejects her love, but all these things changed her life. But her willingness to live and her determination helps her to overcome over her disorder.